2015
DOI: 10.1002/mus.24573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment OF aged mdx mice by electrical impedance myography and magnetic resonance imaging

Abstract: Given the low cost of EIM and the simplicity of application, it may be a valuable alternative to muscle MRI in Duchenne muscular dystrophy, where simple cumulative indices of muscle health are being sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…With the further development of the technique (for example, the custom-designed EIM apparatus), we may evaluate a variety of different surface muscles to gain a more global evaluation of the disease in the dog model; (4) in this study, we have focused on correlating the pathological findings with the EIM data, there is a need to determine whether the EIM data relate well with the results of physiological assays such as muscle force measurement, gait analysis and activity monitoring in dogs [12, 17, 18]; results in mdx mice (Seward B. Rutkove, unpublished results) and ALS mice suggest a relationship between muscle force measurement and impedance values [26]. Similarly, it will be worthwhile to compare EIM with muscle ultrasound and MRI [38, 40]; (5) as a cross-sectional study, we only selected two age groups. To establish a robust natural history profile for the entire population of normal and affected dogs, we are obligated to conduct longitudinal follow-up studies on a large cohort of dogs; (6) as our ultimate goal is to develop an effective therapy for DMD, it will be necessary to implement the EIM assay in preclinical therapy studies to help quantify the efficacy of novel experimental interventions.…”
Section: Discussionmentioning
confidence: 99%
“…With the further development of the technique (for example, the custom-designed EIM apparatus), we may evaluate a variety of different surface muscles to gain a more global evaluation of the disease in the dog model; (4) in this study, we have focused on correlating the pathological findings with the EIM data, there is a need to determine whether the EIM data relate well with the results of physiological assays such as muscle force measurement, gait analysis and activity monitoring in dogs [12, 17, 18]; results in mdx mice (Seward B. Rutkove, unpublished results) and ALS mice suggest a relationship between muscle force measurement and impedance values [26]. Similarly, it will be worthwhile to compare EIM with muscle ultrasound and MRI [38, 40]; (5) as a cross-sectional study, we only selected two age groups. To establish a robust natural history profile for the entire population of normal and affected dogs, we are obligated to conduct longitudinal follow-up studies on a large cohort of dogs; (6) as our ultimate goal is to develop an effective therapy for DMD, it will be necessary to implement the EIM assay in preclinical therapy studies to help quantify the efficacy of novel experimental interventions.…”
Section: Discussionmentioning
confidence: 99%
“…All in vivo animal work reported to date, for example, in amyotrophic lateral sclerosis and muscular dystrophy mice, has been performed on adult animals and has used surface electrode arrays, analogous to those used in human studies (Ahad and Rutkove, 2010; Ahad et al, 2009; Ahad and Rutkove, 2009; Li et al, 2014a; Li et al, 2014d; Li et al, 2013; Li et al, 2012; Wu et al, 2015). Prior studies have demonstrated that subcutaneous tissue contributes little to the measurement of EIM reactance(Sung et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed consistent and significant differences in 50 kHz phase reactance and resistance values between wild-type and mdx mice [8]. In this animal model, EIM values also correlated to muscle fiber size, the amount of connective tissue deposition [8], and also to T2 signal on magnetic resonance imaging (MRI) [92]. EIM has also shown sensitivity to the impact of myostatin inhibition in both wildtype and mdx mice [93].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 86%